Liver cirrhosis mortality at national and provincial levels in Iran between 1990 and 2015: A meta regression analysis - Rezaei, Negar (PLoS One, 2019)
BACKGROUND: Liver cirrhosis mortality number has increased over the last decades. We aimed to estimate the liver cirrhosis mortality rate and its trends for the first time by sex, age, geographical distribution, and cause in Iran. METHOD: Iranian Death Registration System, along with demographic (Complete and Summary Birth History, Maternal Age Cohort and Period methods) and statistical methods (Spatio-temporal and Gaussian process regression models) were used to address the incompleteness and misclassification and uncertainty of death registration system to estimate annual cirrhosis mortality rate. Percentages of deaths were proportionally redistributed into cirrhosis due to hepatitis B, C and alcohol use based on the data from the Global Burden of Disease (GBD) 2010 study. RESULTS: Liver cirrhosis mortality in elder patients was 12 times higher than that in younger patients at national level in 2015. Over the 26 years, liver cirrhosis mortality in males has increased more than that in females. Plus, the percentage of change in age adjusted mortality rate at provincial levels varied between decreases of 64.53% to nearly 17% increase. Mortality rate has increased until 2002 and then decreased until 2015.The province with highest mortality rate in 2015 has nearly two times greater rate compare to the lowest. More than 60% of liver cirrhosis mortality cases at national level are caused by hepatitis B and C infection. The rate of hepatitis B mortality is four times more than that from hepatitis C. CONCLUSION: This study demonstrated an increasing and then decreasing pattern in cirrhosis mortality that could be due to national vaccination of hepatitis B program. However monitoring, early detection and treatment of risk factors of cirrhosis, mainly in high risk age groups and regions are essential. Cirrhosis mortality could be diminished by using new non-invasive methods of cirrhosis screening, hepatitis B vaccination, definite treatment of hepatitis C.